1998
DOI: 10.1007/bf02788830
|View full text |Cite
|
Sign up to set email alerts
|

Conformational stability and antibody response to the 18kda heat- shock protein formulated into different vehicles

Abstract: Protein stability is one of the most important obstacles for successful formulation in the development of new-generation vaccines. Here, the 18kDa heat-shock protein (18kDa-hsp) was chemically modified though conjugation with bovine serum albumin or by esterification with N-hydroxysuccinimide ester of palmitic acid. The biologically active conformation of the protein was preserved after chemical modification. The immune responses to the recombinant 18kDa-hsp from Mycobacterium leprae were studied in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, the functional behaviour of wildtype HSP18 (HSP18S 52 ) is still not understood properly. Despite having less idea about the functionality of wild-type HSP18, this sHSP has been used for the development of second-generation vaccines for leprosy as a carrier protein [29]. Very few attempts have been FEBS Journal 280 (2013) 5994-6009 ª 2013 FEBS made to understand the structure of this protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the functional behaviour of wildtype HSP18 (HSP18S 52 ) is still not understood properly. Despite having less idea about the functionality of wild-type HSP18, this sHSP has been used for the development of second-generation vaccines for leprosy as a carrier protein [29]. Very few attempts have been FEBS Journal 280 (2013) 5994-6009 ª 2013 FEBS made to understand the structure of this protein.…”
Section: Introductionmentioning
confidence: 99%
“…Mitra et al [30] identified tryptic digested fragments in M. leprae HSP18, which appeared to be a potent stimulator of CD4 + T-cell responses in normal and leprotic patients. Costa et al [29] showed that the native conformation of wild-type HSP18 was preserved after hydrophobic modification by acylation. We also made an attempt to understand the structure of wild-type and mutant HSP18 and theoretically demonstrated that mutant HSP18 variant (HSP18P 52 ) has a different secondary structure compared to that of the wild-type HSP18 ( HSP18S 52 ) [31].…”
Section: Introductionmentioning
confidence: 99%
“…We developed the large-scale production of 18 kDa-hsp at low cost in order to be able to introduce this T cell stimulation into our vaccines (7,8). Our main goal was to co-encapsulate the 18 kDa-hsp together with poor antigens within safe and pluripotent supports, such as liposomes (9,10) or biodegradable microspheres (11). These supports can also be excellent vehicles with adjuvant and controlled release capacity.…”
mentioning
confidence: 99%
“…To make this association with the liposome membrane possible, the 18 kDa-hsp was modified by acylation of the lysine residues to increase its hydrophobicity (9). The N-acyl-18 kDa-hsp circular dichroism spectra were obtained using a JASCO spectropolarimeter model J720.…”
mentioning
confidence: 99%
See 1 more Smart Citation